Plastome phylogenomics provide new perspective into the phylogeny and evolution of Betulaceae (Fagales) - Yang, Zhen; Ma, Wenxu; Yang, Xiaohong; Wang, Lujun; Zhao, Tiantian; Liang, Lisong; Wang, Guixi; Ma, Qinghua (BMC plant biology, 2022)
Betulaceae is a relatively small but morphologically diverse family, with many species having important economic and ecological values. Although plastome structure of Betulaceae has been reported sporadically, a comprehensive exploration for plastome evolution is still lacking. Besides, previous phylogenies had been constructed based on limited gene fragments, generating unrobust phylogenetic framework and hindering further studies on divergence ages, biogeography and character evolution. Here, 109 plastomes (sixteen newly assembled and 93 previously published) were subject to comparative genomic and phylogenomic analyses to reconstruct a robust phylogeny and trace the diversification history of Betulaceae. All Betulaceae plastomes were highly conserved in genome size, gene order, and structure, although specific variations such as gene loss and IR boundary shifts were revealed. Ten divergent hotspots, including five coding regions (P > 0.02) and five noncoding regions (P > 0.035), were identified as candidate DNA barcodes for phylogenetic analysis and species delimitation. Phylogenomic analyses yielded high-resolution topology that supported reciprocal monophyly between Betula and Alnus within Betuloideae, and successive divergence of Corylus, Ostryopsis, and Carpinus-Ostrya within Coryloideae. Incomplete lineage sorting and hybridization may be responsible for the mutual paraphyly between Ostrya and Carpinus. Betulaceae ancestors originated from East Asia during the upper Cretaceous; dispersals and subsequent vicariance accompanied by historical environment changes contributed to its diversification and intercontinental disjunction. Ancestral state reconstruction indicated the acquisition of many taxonomic characters was actually the results of parallel or reversal evolution. Our research represents the most comprehensive taxon-sampled and plastome-level phylogenetic inference for Betulaceae to date. The results clearly document global patterns of plastome structural evolution, and established a well-supported phylogeny of Betulaceae. The robust phylogenetic framework not only provides new insights into the intergeneric relationships, but also contributes to a perspective on the diversification history and evolution of the family.